Prognostic value of visceral pleural invasion in non‐small cell lung cancer: A propensity score matching study based on the SEER registry. Issue 3 (22nd May 2017) - Yang, Xiaodong; Sun, Fenghao; Chen, Li; Shi, Mengkun; Shi, Yu; Lin, Zongwu; Feng, Mingxiang; Zhan, Cheng; Jiang, Wei; Wang, Qun
Abstract : Background and Objectives: Visceral pleural invasion (VPI) is considered a poor prognostic factor in non‐small cell lung cancer (NSCLC). We aimed to analyze the effect of VPI on cancer‐specific survival, using propensity score matching (PSM) based on the Surveillance, Epidemiology, and End Results database. Methods: We identified 9901 patients with T1‐2N0‐2M0 who received segmentectomy, lobectomy, or pneumonectomy. Ten covariates were included in PSM. The effect of VPI on survival was assessed, stratified by nodal status and tumor size. Results: One‐thousand and eighty‐three pairs of patients were matched with standardized differences of covariates <10% after matching. We found that VPI was associated with a significantly worse survival (3‐year survival rate: 84.6% vs. 75.9%, P  = 0.005), especially in N0 ( P  < 0.001), but not in N1 or N2. No significant difference was observed between the extent of VPI. Moreover, VPI conferred a significantly worse survival in tumors >1‐2 ( P  = 0.034) and >2–3 cm ( P  < 0.001), not ≤1, >3‐4, or >4‐5 cm in N0. Conclusions: VPI is a poor prognostic factor; but with increasing tumor size and nodal stage, its negative effect disappears. Our findings support current staging system which assigns higher T‐stage for early >1‐2 and >2‐3 cm tumors.